Primary human osteoblast culture on 3D porous collagen-hydroxyapatite scaffolds. - Jones, G; Walton, R; Czernuszka, J; Griffiths, S; El Haj, A; Cartmell, S (2010)
There is a need in tissue-engineering for 3D scaffolds that mimic the natural extracellular matrix of bone to enhance cell adhesion, proliferation, and differentiation. The scaffold is also required to be degradable. A highly porous scaffold has been developed to incorporate two of the extracellular components found in bone-collagen and hydroxyapatite (HA). The scaffold's collagen component is an afibrillar monomeric type I atelocollagen extracted from foetal calf's skin. This provided a novel environment for the inclusion of HA powder. Five hundred thousand primary human osteoblasts were seeded onto 4 mm cubed scaffolds that varied in ratio of HA to collagen. Weight ratios of 1:99, 25:75, 50:50, and 75:25 hydroxyapatite:collagen (HA:Collagen) were analysed. The scaffolds plus cells were cultured for 21 days. DNA assays and live/dead viability staining demonstrated that all of the scaffolds supported cell proliferation and viability. An alkaline phosphatase assay showed similar osteoblast phenotype maintenance on all of the 3D scaffolds analysed at 21 days. MicroCT analysis demonstrated an increase in total sample volume (correlating to increase in unmineralised matrix production). An even distribution of HA throughout the collagen matrix was observed using this technique. Also at 3 weeks, reductions in the percentage of the mineralised phase of the constructs were seen. These results indicate that each of the ratios of HA/collagen scaffolds have great potential for bone tissue engineering.